2014
DOI: 10.4236/pp.2014.58091
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Anticancer Activity of Plant-Derived Cannabidiol on Prostate Cancer Cell Lines

Abstract: Cannabinoids, the active components of Cannabis sativa Linnaeus, have received renewed interest in recent years due to their diverse pharmacologic activities such as cell growth inhibition, anti-inflammatory effects and tumor regression, but their use in chemotherapy is limited by their psychotropic activity. To date, cannabinoids have been successfully used in the treatment of nausea and vomiting, two common side effects that accompany chemotherapy in cancer patients. Most non-THC plant cannabinoids e.g. cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
2
41
1
1
Order By: Relevance
“…Furthermore, these effects are mediated by the modulation of the ERK and AKT signaling pathways [90]. CBD (at 0.5-7 µl/mL) inhibits the spheroid formation and dow-nregulates CB1 and CB2 receptors, VEGF, PSA, and pro-inflammatory cytokines IL-6/IL-8 in LNCaP prostate cancer stem cells [91]. In vivo, CBD-enriched cannabis extract (1-100 mg/kg −1 ) reduced tumor size in LNCaP-xenografted mice and enhanced the anticancer effect of bicalutamide (50 mg/kg −1 ), but not of docetaxel (5 mg/kg −1 ), while in DU-145 xenografts CBD was inactive alone but able to potentiate the effect of docetaxel [92].…”
Section: Breast and Prostate Cancersmentioning
confidence: 99%
“…Furthermore, these effects are mediated by the modulation of the ERK and AKT signaling pathways [90]. CBD (at 0.5-7 µl/mL) inhibits the spheroid formation and dow-nregulates CB1 and CB2 receptors, VEGF, PSA, and pro-inflammatory cytokines IL-6/IL-8 in LNCaP prostate cancer stem cells [91]. In vivo, CBD-enriched cannabis extract (1-100 mg/kg −1 ) reduced tumor size in LNCaP-xenografted mice and enhanced the anticancer effect of bicalutamide (50 mg/kg −1 ), but not of docetaxel (5 mg/kg −1 ), while in DU-145 xenografts CBD was inactive alone but able to potentiate the effect of docetaxel [92].…”
Section: Breast and Prostate Cancersmentioning
confidence: 99%
“…In addition to THC, CBD is another plant-derived cannabinoid that has been extensively studied for its potential antitumor effects [39,[65][66][67][68]. In a panel of human prostate cancer cell lines, Sharma et al [67] showed that CBD is a potent inhibitor of cancer cell growth, while this potency was significantly lower in non-cancer cells.…”
Section: Plant-derived Cannabinoids and Their Antitumor Activitymentioning
confidence: 99%
“…The result showed that prostate cancer cell lines clearly indicate that cannabidiol is a potent inhibitor of cancer cell growth with significantly lower potency in noncancer cells. The mRNA expression level of cannabinoid receptors CB1 and CB2, vascular endothelial growth factor (VEGF), PSA (prostate specific antigen) are significantly higher in human prostate cell lines [33].…”
Section: Sharma Et Al (2014)mentioning
confidence: 99%